THE AUTHORITY OF MORAL OVERSIGHT: ON THE LEGITIMACY OF CRIMINAL LAW. (September 2019) - Bennett, Christopher
ABSTRACT: An influential view in recent philosophy of punishment is that the apparatus of criminal justice should be geared at least in part to state censure of wrongdoing. I argue that if it were to be so geared, such an apparatus would make ambitious claims to authority, and that the legitimacy of the relevant state would then depend on whether those claims can be vindicated. This paper looks first at what kind of authority is being claimed by this apparatus. The criminal law, I argue, cannot merely be thought of as claiming a right to rule and to be obeyed. Rather, its authority is better understood as the authority of moral oversight : a power to alter, at will (though within certain limits), citizens' liability to answer for their compliance with—and to be officially censured for their failure to comply with—a designated set of pre-existing moral 7reasons. The paper then looks at whether a state could realistically be expected to possess such authority—that is, whether a state that claims to have such a power could ever be legitimate.